2004
DOI: 10.1080/00016350310008012
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of dentin induced by treatment with bioactive glass S53P4 in vitro

Abstract: Dentin hypersensitivity can be managed to occlude dentin tubules, but none of the agents used are components of natural dentin. Using a calcium phosphate precipitation (CPP) method, dentin tubules can be occluded with a calcium phosphate (CaP) layer similar to the major inorganic component of dentin. The CPP method utilizes acidic pH conditions, such as etching of dentin, over the course of several dental treatments. A gentler method can be used to produce a CaP layer on the surface of dentin. By treating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
18

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 21 publications
1
78
1
18
Order By: Relevance
“…For bonelike apatite coating on materials with complex shapes, it was reported that an apatite layer was formed when sodium silicate was used as a catalyst for apatite nucleation -whereby particular silicate oligomers with structures such as dimer, linear trimer, and cyclic tetramer contributed most to apatite nucleation 29) . On its contribution to dentin mineralization, it was reported that Si promoted dentin mineralization by a mechanism based on the condensation of silicic acid to oligomers 30) . When a sufficient quantity of Si was adsorbed on dentin with anionic groups (SiO − ), it acted as a nucleation centre for subsequent, increased CaP formation 30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bonelike apatite coating on materials with complex shapes, it was reported that an apatite layer was formed when sodium silicate was used as a catalyst for apatite nucleation -whereby particular silicate oligomers with structures such as dimer, linear trimer, and cyclic tetramer contributed most to apatite nucleation 29) . On its contribution to dentin mineralization, it was reported that Si promoted dentin mineralization by a mechanism based on the condensation of silicic acid to oligomers 30) . When a sufficient quantity of Si was adsorbed on dentin with anionic groups (SiO − ), it acted as a nucleation centre for subsequent, increased CaP formation 30) .…”
Section: Discussionmentioning
confidence: 99%
“…On its contribution to dentin mineralization, it was reported that Si promoted dentin mineralization by a mechanism based on the condensation of silicic acid to oligomers 30) . When a sufficient quantity of Si was adsorbed on dentin with anionic groups (SiO − ), it acted as a nucleation centre for subsequent, increased CaP formation 30) . In the present study, pH measurements indicated that S-PRG filler altered the pH values of both distilled water and lactic acid solution closer to neutral.…”
Section: Discussionmentioning
confidence: 99%
“…Another route of caries treatment is related to stop the disease and trying to re-mineralize the dentin and enamel with the aim to re-establish the natural tooth or at least significant parts of it [65][66][67]. Here, nanotechnology might be of upmost importance as nanometer-size calcium phosphates tend to nucleate at the nanometer-size collagen fibrils [68,69].…”
Section: Bio-inspired Treatments Of Teeth: Nanodentistrymentioning
confidence: 99%
“…59 Temel bileşeni silika olup, kalsiyum ve fosfatın çökelmesi için çekir-dek görevi gören bioaktif camların SEM çalış-malarında dentin kanallarını tıkayan apatit bir tabaka olarak gözlendiği bildirilmiştir. 60 DH tedavisinde kullanılan bioaktif camlar Novamin (Novamin Technology Inc., FL, USA) olarak bilinen ürün şeklinde kullanıma girmiştir.…”
Section: Bioaktif Camlarunclassified